Advances in Business and Management Forecasting. Vol. 12 - Lawrence, Kenneth D.; Klimberg, Ronald K. (Advances in business and management forecasting ;, 2017)
Volume 12, Advances in Business and Management Forecasting, is a blind refereed serial publication. It presents state-of-the-art studies in the application of forecasting methodologies to such areas as supply chain, health care, prospecting for donations from university alumni, and the use of clustering and regression in forecasting. The orientation of this volume is for business applications for both the researcher and the practitioner of forecasting. Volume 12 is divided into three sections: Forecasting Applications, Predictive Analytics and Time Series. An interdisciplinary group of experts explore wide-ranging topics including multi-criteria scoring models, detecting rare events, the assessment of control charts for intermittent data, and fuzzy time series models.